Beyond Time and Place: Why Autonomy Flexibility is the Real Driver of Engagement in the Public Sector - Hari Nugraha; Muhammad Taufiq; Iin Agustina (Trescode Green Organization, 2026)
This research aims to explore the intricate relationship between Flexible Work Arrangements (FWA) and Job Engagement within the specific context of the public sector in Bandung, Indonesia. In an era of rapid digital transformation and evolving bureaucratic demands, understanding how work design influences civil servant motivation is crucial. This study employs a quantitative research design, deconstructing FWA into three distinct dimensions—time flexibility, place flexibility, and autonomy flexibility—while measuring job engagement through the components of vigor, dedication, and absorption. Data were systematically collected from 71 public sector employees through online surveys supported by field enumerators to ensure data integrity. The results of the multiple regression analysis reveal a significant paradigm shift in how engagement is cultivated in public organizations. Findings indicate that autonomy flexibility is the sole significant predictor of job engagement, specifically exerting a strong positive influence on dedication and absorption. Conversely, time and place flexibility were found to be statistically insignificant across all engagement dimensions. This suggests that for public sector employees, psychological empowerment and procedural control are far more valuable than logistical convenience. These results highlight that autonomy acts as a primary catalyst for public service motivation and proactive work behavior. Practically, government agencies are advised to transition from rigid compliance-based management to trust-based job redesigns that prioritize task autonomy to foster a highly focused and dedicated workforce.